Credit Spreads und ihre Determinanten: Eine empirische Analyse für Deutschland - Horst Rottmann; Franz Seitz (Kredit und Kapital, 2008)
– Credit Spreads and their Determinants: An Empirical Analysis for Germany Analyses of credit spreads, i. e. the difference between the returns on corporate loans and on no-risk investments for periods equivalent in length, can provide useful information to both business managers and to external observers. In this article, fundamental determinants of such credit spreads have been defined in theoretical terms and been subjected to empirical review on the basis of fixed-rate loan issues of non-financial DAX enterprises. At the micro-econometrics level, a new set of data for Germany has been used for taking account of empirically observable market characteristics in adequate panel methods. In this context, a structural model has been combined with a reduced form approach. Compared to traditional approaches, the result is a significantly better explanation based on economically provable variables.
Keywords: 330